Working Natures: An Ethnography of Love, Labour, and Accumulation on the British Columbian Coast - Yard, Jaime Dianne (York University, 2013)
The primary question for investigation throughout this research is how the environmental knowledges of settler-colonists and their descendants have been formed through processes of work and dwelling in place. This dissertation results from over a year of fieldwork in an aging community where retired loggers, semi-retired fishermen, and retired exurban migrants are actively renegotiating the meanings of local places and natures as the local economy shifts from a base in logging and fishing to one in recreational and retirement real estate development. Through archival research, life history interviews and participant-observation with loggers, fishermen, exurban retirees and other long-term residents I explored the complications and contradictions inherent in learning to value nature through processes of transforming and intervening in ecological processes for economic ends. Writing against hard social constructivism I examine the ways in which the life cycles of fish and fish populations, the contingencies of weather, topography and currents, and, the physical form of the land are active elements in the formation of labour and settlement patterns in coastal British Columbia. As a contribution to the underdeveloped field of first world political ecology this work maps environmental knowledges and values developed in tense complicity with regimes of natural resource management and accumulation by dispossession. Central to this process is how people become agents of the commodification of nature and place in their everyday lives and work, and, how private property has become naturalized as a prerequisite to "protecting" self, nature, and community from precarity in the era of late capitalism. This dissertation tracks the various ways, both historically and in the present, that settlers and their descendants on the BC Coast have attempted to simultaneously make a living and make a home of an occupied place-the imperialist nostalgia and (neo)liberal white guilt endemic to the process.
Keywords: British Columbia; Commodification of nature; Environmental knowledge; Labor; Settler-colonists; Social sciences